High protein sorghum grain with no added protein in all concentrate cattle finishing rations; Urea and soybean oil meal in all concentrate rations - Smith, E.F.; Richardson, D.; Drake, C.L.; Brent, B.E. (Kansas State University. Agricultural Experiment Station, 2011)
Trials at several research centers as well as in Kansas (Bulletin 483, page 32) have shown roughage may be satisfactorily omitted from finishing rations for cattle and doing so, often reduces feed required per pound of gain. That has made it feasible to try to finish cattle on all grain diet5, when the grain has sufficient protein, and to omit other protein sources as well as roughage. Other research on this subject is reported in Kansas Bulletins 493 and 507 and on page in this bulletin.
Keywords: Beef; Protein; Sorghum grain; Finishing rations; Urea; Soybean oil